The Effects of Stimulus Package, Lockdown and Positive Cases of COVID-19 on the Stock Returns in the U.S. and U.K. - Xie, Ruifeng (2020)
The pandemic of COVID-19, which spreads to almost the whole world, has decreased the global GDP of 2020 by 3.3% (The World Bank, 2021), and it is predicted to decrease the global GDP of 2021 by 5.2% (International Monetary Fund, 2020). During this unprecedented pandemic, the stock markets became much more risky and volatile. As the pandemic is predicted to keep going for a longer time, it is critical for the government and investors to understand how the pandemic affects the stock markets. Knowing that relationship may help them to find better methods to control and reduce the risk of stock markets in the future. Based on existing findings, we conduct an analysis of how the stimulus packages, lockdown policies, cumulative positive cases of COVID-19 and growth rate of cases affect the stock returns in the U.S. and U.K. during the pandemic. Our main findings suggest that the lockdown policies and positive cases have positive impacts on the stock markets in the U.S. and U.K., but only the U.K. stock market negatively respond to the growth rate of cases. Moreover, we find the stimulus packages do not affect both markets. Further, our results suggest that the events do not have different effects on small and large capitalization stocks in both countries.